2015
DOI: 10.1016/j.eurpsy.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic occupation assessment of executive function in adolescents with schizophrenia spectrum disorders: An initial report

Abstract: The DOAEF may be useful in assessing the level of mediation, which patients need for the comprehension of daily situations in which EFs are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The reported reliability and validity of each of these six measures of EF is presented in Table 4. In summary, their internal consistency ranged between 0.60 and 0.97 (acceptable to excellent); only one study (Chubarov et al, 2015) reported inter-rater reliability and test-retest reliability (for DOAEF) as 0.97 and 0.91, respectively; only one study (Duke et al, 2014) reported inter-informant reliability (for DREFS) as 0.73. Validity aspects that were examined for some of these six measures included construct, convergent, discriminant, and concurrent validities.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported reliability and validity of each of these six measures of EF is presented in Table 4. In summary, their internal consistency ranged between 0.60 and 0.97 (acceptable to excellent); only one study (Chubarov et al, 2015) reported inter-rater reliability and test-retest reliability (for DOAEF) as 0.97 and 0.91, respectively; only one study (Duke et al, 2014) reported inter-informant reliability (for DREFS) as 0.73. Validity aspects that were examined for some of these six measures included construct, convergent, discriminant, and concurrent validities.…”
Section: Resultsmentioning
confidence: 99%
“…The six additional rating scales with reported psychometrics were: the Dynamic Occupation Assessment of Executive Function (DOAEF; Chubarov et al, 2015); Diabetes Related Executive Functioning Scale (DREFS; Duke et al, 2014); Behavioral Inhibition System and Behavioral Activation System (BIS/BAS; Carver and White, 1994); EpiTrack Junior® (Kadish et al, 2013); Amsterdam Executive Function Inventory (AEFI; Van der Elst et al, 2012); and Ballet Executive Scale (BES; Wong et al, 2012). The reported reliability and validity of each of these six measures of EF is presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations